Wondering + online inquiry = learning - Diane Carver Sekeres; Julie Coiro; Jill Castek; Lizabeth A. Guzniczak (Phi Delta Kappan, 2014)
Learning what happens as elementary school children read and make meaning of the text and images they see is fascinating, especially when the reading is done in the context of children’s interactions with each other and with online information. But such online inquiry tends to happen with students sitting closely together at a computer or a tablet, when all you can see is the backs of their heads. So how do we know the time they’re spending in inquiry is productive? What influence does a project’s design have on children’s work? Is the chatter that we hear helpful for their thinking and learning? We have found carefully structured tasks that scaffold the ability to question, navigate, and negotiate the meaning of online text, and we have discovered that images can foster collaborations that are engaging, deeply comprehensive, and fruitful (Coiro et al., 2014). Inquiry-based learning engages students in collecting information, analyzing data, and crafting presentations that create solutions or make arguments. Students be come more positive and independent in their learning while gaining new knowledge and meaningful understandings of their world. Yet designing assignments that scaffold inquiry is often necessary to support students’ efforts. Structured inquiry experiences can help learners develop skills for coping with problems that have no clear solutions, dealing with challenges, and adapting procedures to the demands of different situations (Alberta Learning, 2004). Our research findings reinforce what others have suggested — that while students follow general patterns in thinking and collaboration, the inquiry process “is not linear or lock step. It is highly individual, nonlinear, flexible, and more recursive than might be suggested in traditional models of the research process” (Alberta Learning, 2004, p. 9). Thus, depending on the purposes of inquiry and the abilities of students, there are different ways to frame inquiries to support student success. Alberta’s model of inquiry-based learning delineates four gradually less restrictive frameworks designed to encourage students’ wondering with authentic inquiry tasks (see Figure 1). We found that the design of a structured online inquiry supports children’s success in grades 3-5. We also uncovered certain patterns in how children read and talk about their work that enable them to be productive during various phases of the inquiry process.

Digging Deeper : Online Reading Comprehension and Collaborative Inquiry. Providence - Julie Coiro; Michelle Schira Hagerman (RI : Summer Institute on Digital Literacy, 2013)
Keywords: compétences; jeunesse; lecture numérique

New Literacies : A Dual-Level Theory of the Changing Nature of Literacy, Instruction, and Assessment - Donald J. Leu; Charles K. Kinzer; Julie Coiro; Jill Castek; Laurie A. Henry (From theorical models and process of reading, 2013)
Literacy as Deixis Today, the nature of literacy has become deictic. This simple idea carries impor-tant implications for literacy theory, research, and instruction that our field mustbegin to address. Deixis is a term used by linguists (Filmore, 1966; Murphy, 1986;Traut & Kazzazi, 1996) to define words whose meanings change rapidly as theircontext changes. Tomorrow, for example, is a deictic term; the meaning of “tomor-row” becomes “today” every 24 hours. The meaning of literacy has also becomedeictic because we live in an age of rapidly changing information and commu-nication technologies, each of which requires new literacies (Leu, 1997, 2000).Thus, to have been literate yesterday, in a world defined primarily by relativelystatic book technologies, does not ensure that one is fully literate today wherewe encounter new technologies such as Google docs, Skype, iMovie, Contribute,Basecamp, Dropbox, Facebook, Google, foursquare, Chrome, educational video-games, or thousands of mobile “apps.” To be literate tomorrow will be defined byeven newer technologies that have yet to appear and even newer discourses andsocial practices that will be created to meet future needs. Thus, when we speak ofnew literacies we mean that literacy is not just new today; it becomes new everyday of our lives.
Keywords: compétences; évaluation; lecture numérique; littératie; littératie numérique

The New Literacies of Online Reading Comprehension : Future Directions - Julie Coiro (The Educational Forum, 2012)
Research in four areas has the potential to dramatically improve how practitioners address the challenges of integrating digital texts and tasks into their literacy curriculum. Advances in defi ning and measuring key componentsof online reading comprehension are rapidly emerging. In addition,instructional models, such acquisition of online reading comprehension, but teachers need access to sustained professional development that is aligned with their own learning goals.   Key words: new literacies, online inquiry, online reading comprehension, online reading, proficiency.
Keywords: compréhension; lecture numérique; littératie

Understanding Dispositions Toward Reading on the Internet - Julie Coiro (2012)

Predicting Reading Comprehension on the Internet: Contributions of Offline Reading Skills, Online Reading Skills, and Prior Knowledge - Julie Coiro (2011)

Exploring the online reading comprehension strategies used by sixth-grade skilled readers to search for and locate information on the Internet - Julie Coiro (Reading Research Quarterly, 2007)
The purpose of this qualitative study was to explore the nature of reading comprehension processes while reading on the Internet. Eleven sixth-grade students with the highest combination of standardized reading scores, reading report card grades, and Internet reading experiences were selected from a population of 150 sixth graders in three different middle schools in the central and northeastern United States. These 11 skilled readers met individually with a researcher and completed two separate tasks that involved reading within multilayered websites or using the Yahooligans! search engine. Students answered specific questions about their strategy use in a follow-up interview after each reading session. Qualitative analysis evolved through four distinct phases, each of which involved reviewing data from think-aloud protocols, field observations, and semistructured interviews to provide insights on the nature of online reading comprehension. Findings suggested that successful Internet reading experiences appeared to simultaneously require both similar and more complex applications of (1) prior knowledge sources, (2) inferential reasoning strategies, and (3) self-regulated reading processes. The authors suggest that reading Internet text prompts a process of self-directed text construction that may explain the additional complexities of online reading comprehension. Implications for literacy theory and future research are discussed. (Contains 5 tables and 4 figures.)
Keywords: compétences; formation à distance; grade 6; stratégie de lecture; stratégies d'apprentissage

Exploring Literacy on the Internet: Reading Comprehension on the Internet: Expanding Our Understanding of Reading Comprehension to Encompass New Literacies - Julie Coiro (2003)